Increasing parents’ knowledge about the effect of parents’ attachment to adolescent stress during the COVID-19 pandemic - Yuliasti Eka Purnamaningrum; Yuni Kusmiyati (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
The Novel Coronavirus Disease 19 (COVID-19) pandemic had a significant impact on human survival. This phenomenon causes changes in various aspects of life such as the teaching and learning process, it moved at home by e-learning and adolescent must experience anxiety, stress or boredom. The purpose of this study is to increase parents' knowledge about the influence of parents' attachment to adolescent stress. The method is an online meeting through a zoom meeting. The study was carried out in Sukoharjo, Ngaglik District, Sleman Regency involving 50 teenagers' parents. There is an influence of parents’ attachment to adolescent stress during the COVID-19 pandemic and the stress level of adolescents depends on their attachment to parents. After 3 months of implementing the mentoring activities, 88 % of the respondents have a good category about the influence of parents’ attachment to adolescent stress during the COVID-19 pandemic.